CONTROL OF LUMINOUS INTENSITY DISTRIBUTION FROM AN ARRAY OF POINT LIGHT SOURCES - ASHDOWN IAN; TISCHLER MICHAEL A (2014)
In various embodiments, a lens array comprises a plurality of aspheric lens elements each optically coupled to a light-emitting element and producing an out-of-focus image thereof. The images combine to generate a target luminous intensity distribution, e.g., providing constant illuminance on a plane.